Content management for e-learning - Ferrer, Núria Ferrer; Alfonso, Julià Minguillón (Springer, 2011)
From the shift to learner-centered education to the sharing of online resources among colleges and universities, virtual learning has brought sweeping change to the educational experience. New information and communication technologies are bringing fresh challenges in terms of organizing and delivering content-particularly with the advent of Web 2.0 and the ability of learners to author their own content. Accordingly, many educators, departments, and institutions are unsure how best to commit the large amounts of money, time, and resources that go into such an upgrade. Content Management for E-Learning offers thorough coverage of the conceptual, technical, pedagogical, and budgetary issues for readers first grappling with the new concepts of information competence as well as those at schools already involved in new technologies and seeking improvements to their current systems. Chapters provide a theoretical and practical framework for effectively providing access to resources, matching content management to knowledge management, and more, including these key features: An overview of the widely-used Learning Content Management System. Case studies in content management projects. A peer evaluation model for open educational resources. Technical standards and specifications for content management. An administrative model for implementing e-learning. Copyright and intellectual property issues involved in producing e-content. Content Management for E-Learning is an up-to-the-minute blueprint and idea book for producers and consumers of learning content (e.g. Students, teachers, lecturers and librarians), for educational institutions and eLearning centers and for those tracking the redefining of teaching and learning or contributing to this process